Determinants of Virologic Failure Among Adults on Second Line Antiretroviral Therapy in Wollo, Amhara Regional State, Northeast Ethiopia - Seid A (Dove Medical Press, 2020)
Ali Seid,1 Niguss Cherie,2 Kemal Ahmed3 1Reproductive and Family Health Unit, Dessie Health Science College, Dessie, Ethiopia; 2Reproductive and Family Health Unit, School of Public Health, College of Medicine and Health Sciences, Wollo University, Dessie, Ethiopia; 3School of Public Health, College of Medicine and Health Sciences, Wollo University, Dessie, EthiopiaCorrespondence: Niguss CherieReproductive and Family Health Unit, School of Public Health, College of Medicine and Health Sciences, Wollo University, PO Box: 1145, Dessie, EthiopiaTel +251 910749743Email nigucheru@gmail.comBackground: Treatment failure among the population on second line antiretroviral therapy is a major public health threat. In Ethiopia there has been limited research done on second line treatment failure.Objective: To identify determinants of virologic failure among adults on second line antiretroviral therapy in six public hospitals of Wollo, Amhara regional state, northeast Ethiopia.Methods: An institution-based unmatched case–control study was conducted from February 1, 2020 to April 30, 2020 on a total of 377 clients in six public hospitals of Wollo, Amhara regional state, northeast Ethiopia. Clients whose viral load result > 1,000 copies/mL in two consecutive results at least 3 month apart were cases, while ≤ 1,000 copies/mL were controls. The sample size was calculated by using Epi-Info version 7. Cases (94) and controls (283) were selected using a simple random sampling method in a ratio of cases-to-controls of 1:3. The model fitted and binary logistic assumptions were fulfilled with 95% confidence level and P-values< 0.05 were taken as statistically significant.Results: Virologic failure was predicted by poor adherence (AOR=6.060, 95% CI=2.837– 12.944), not disclosing their HIV status (AOR=4.178, 95% CI=1.431– 12.198), OI (AOR=4.11, 95% CI=1.827– 9.246), CD4 count < 100 cells/mm3 (AOR=3.497, 95% CI=1.233– 9.923) and 100– 350 cells/mm3 (AOR=5.442, 95% CI=2.191– 13.513), low BMI < 16 kg/m2 (AOR=7.223, 95% CI=2.218– 23.520), and young age 15– 29 years (AOR=2.898, 95% CI=1.171– 7.170).Conclusion and Recommendations: Determinants of second line ART virologic failure were patients who had poor adherence to ART, not disclosed, opportunistic infection, low CD4 counts < 350 cell/mm3, low BMI (< 16 kg/m2), and young age 15– 29 year patients. Social support, disclosing their HIV status, and getting early treatment for any opportunistic infection is crucial to patients.Keywords: HIV, second line ART, virologic failure, case–control study, Wollo, northeast Ethiopia